Proceedings of the second international meeting on endemic mycoses of the Americas (IMEMA) and first international symposium on implantation mycoses (ISIM) (2024)
The second international meeting on endemic mycoses of the Americas (IMEMA) and the first international symposium on implantation mycoses (ISIM) took place in Santiago del Estero, Argentina, on September 25-27, 2023. The conference provided a platform for researchers, clinicians, and experts to discuss the latest developments in the field of endemic and implantation mycoses. Topics included epidemiology, diagnostic advances, treatment strategies, and the impact of environmental factors on the spread of these fungal diseases. IMEMA and ISIM contributed to the regional discourse on the mycoses, emphasizing the importance of international cooperation in addressing these public health challenges.